2022
DOI: 10.3390/pharmaceutics14081680
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanoparticles Based on Iron Oxide and Gold-198 Designed for Magnetic Hyperthermia and Radionuclide Therapy as a Potential Tool for Combined HER2-Positive Cancer Treatment

Abstract: Iron oxide nanoparticles are commonly used in many medical applications as they can be easily modified, have a high surface-to-volume ratio, and are biocompatible and biodegradable. This study was performed to synthesize nanoparticles designed for multimodal HER2-positive cancer treatment involving radionuclide therapy and magnetic hyperthermia. The magnetic core (Fe3O4) was coated with a gold-198 layer creating so-called core-shell nanoparticles. These were then further modified with a bifunctional PEG linker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
4
15
0
Order By: Relevance
“…A very low signal was detected inside the cells (panel E/2), which may suggest the passive transport of particles. The obtained results were consistent with our previously reported studies with the AuNPs–Tmab bioconjugate [ 19 , 20 , 21 , 24 ] as well as data published by other groups [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…A very low signal was detected inside the cells (panel E/2), which may suggest the passive transport of particles. The obtained results were consistent with our previously reported studies with the AuNPs–Tmab bioconjugate [ 19 , 20 , 21 , 24 ] as well as data published by other groups [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…Nevertheless, they demonstrated the use of 131 I-APTES functionalized SPION without magnetic-induced hyperthermia was sufficient to induce a significant lowering of the tumor growth rate [ 208 ]. Similarly, Zuk et al explored the potential of SPION containing a radioactive isotope of gold and functionalized with trastuzumab in order to target HER-2 positive cancer cells [ 209 ]. This strategy allowed the authors to induce a significant regression of spheroid growth.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Cytotoxicity studies with 47 Sc were performed with MTS assay according to the previously reported protocol [5]. LNCaP (10 x 10 3 ) and PC-3 (7.5 x 10 3 ) cells were seeded into 96-well plates 48 h before treatment and incubated in 37°C with 5% CO2-supplemented atmosphere.…”
Section: Mts Assaymentioning
confidence: 99%
“…In another publication 223 Ra-doped BaFe nanoparticles were presented as candidates for multimodal drug combining localized magnetic hyperthermia with internal α-therapy [4]. Magnetic nanoparticles labeled also with βemitters ( 188 Re, 198 Au, 90 Y, and 131 I) and Auger electrons emitters ( 111 In, 125 I) were also investigated, some of them in preclinical studies [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation